Occupational Hazards and Safety Practices among Woodworkers in Sokoban Wood Village, Ghana - Opoku Agyemang, Cecilia; Oscar Agyemang Opoku (Journal of Public Health Sciences, 2025)
The study determined the knowledge of workers on occupational health hazards and safety practices at Sokoban Wood Village in Ghana. A descriptive design with a quantitative approach was adopted. The study employed convenience sampling of the non-probability technique to select respondents to participate in the study. Data was collected from 83 respondents using structured questionnaires and analyzed descriptively with the aid of SPSS software. These findings shed light on the potential risks and challenges faced by the participants, highlighting the importance of occupational safety measures and health education to mitigate these hazards. Woodworkers were aware of occupational hazards associated with their work. The lack of proactive measures in response to noise pollution and the reliance on self-medication for airway-related ailments highlight the need for improved awareness, education, and healthcare services. It was recommended, among other things, that the leaders and managers should link up with local health authorities to provide comprehensive training programs that educate woodworkers about the potential hazards they face in their occupation, particularly related to sawdust and noise exposure.